The Effect of Human Activities on Raptors: A Preliminary Study on Samples of Wildlife Rehabilitation Center - Kandir, Emine Hesna; Gül, Tuğrul Çağrı; Saraçoğlu, Beste (Progress in Nutrition, 2021)
Study Objectives: Raptors are species playing a role in critical ecological functions, supporting human societies as the bio indicator of environmental health and tending to be extinct. Human factors affect the entire ecosystem as well as raptors. The aim of this study was to determine why raptors were brought to a wildlife center in Turkey and to detect outcomes. In this study, records of 348 raptors within Falconiformes and Strigiformes orders admitted to a wildlife rehabilitation center between 2017-2020 were studied. Methods: In this study, we analyzed raptors by taking the following factors into account: year of admission; order (Falconiformes or Strigiformes); species; season; cause of admission; type of landscape; hunting season or not; raptor outcomes. The relationships between variables were determined by the Chi-Square test. The statistical significance level was taken as 0.05. Results: According to the results of this study, the increase in the number of raptors affected by threats over the years was considered significant (p<0.01). One of the anthropogenic based threats; trauma was considered carrying the highest risk (40.2%) in both orders while the second one was detected as a condition disorder. The third one was firearms injuries for Falconiformes (14.2%) and orphans (22%) for Strigiformes. Wintering season has been full of threats for both orders (p<0.01). While Falconiformes faced more threats in suburban areas (p<0.01), the locality was found to be insignificant in Strigiformes based on threats (p>0.05). The relation between threats and outcomes in Falconiformes was found highly important (p<0.01) and the highest mortality rate was stated as 75.6% by firearms injuries and the release rate 86.2% for the orphan. A crucial relation was detected between hunting season and threats (p<0.01) and gun shooting injuries were found the highest for both orders during this period. Conclusion: It was concluded that threats from human interaction on Raptors in Turkey are at a serious level.